Novel and conventional inhibitors of canonical autophagy differently affect LC3‐associated phagocytosis. Issue 4 (21st January 2022) - Stempels, Femmy C.; Janssens, Maaike H.; ter Beest, Martin; Mesman, Rob J.; Revelo, Natalia H.; Ioannidis, Melina; van den Bogaart, Geert
Abstract : In autophagy, LC3‐positive autophagophores fuse and encapsulate the autophagic cargo in a double‐membrane structure. In contrast, lipidated LC3 (LC3‐II) is directly formed at the phagosomal membrane in LC3‐associated phagocytosis (LAP). In this study, we dissected the effects of autophagy inhibitors on LAP. SAR405, an inhibitor of VPS34, reduced levels of LC3‐II and inhibited LAP. In contrast, the inhibitors of endosomal acidification bafilomycin A1 and chloroquine increased levels of LC3‐II, due to reduced degradation in acidic lysosomes. However, while bafilomycin A1 inhibited LAP, chloroquine did not. Finally, EACC, which inhibits the fusion of autophagosomes with lysosomes, promoted LC3 degradation possibly by the proteasome. Targeting LAP with small molecule inhibitors is important given its emerging role in infectious and autoimmune diseases. Abstract : In autophagy, LC3 decorates double‐membrane structures. In contrast, in LC3‐associated phagocytosis (LAP), LC3 is recruited to the single phagosomal membrane. We dissected the effects of four autophagy inhibitors on LAP in monocyte‐derived dendritic cells. VPS34 inhibitor SAR405 and lysosomal inhibitor bafilomycin A1 decreased LAP. However, lysosomal inhibitor chloroquine and autophagosome–lysosome fusion inhibitor EACC.